Culturas e comunicações do universo plus size: uma cartografia das imagens de corpo nos discursos nas redes sociais - Nechar, Patrícia Assuf (2015)
The purpose of this Master s thesis is to study the social media s discourses regarding the fat body, especially those circulating in blogs associated with the plus size universe. Inserted in the field of communication and following the processes of creation in media and culture line of research, this study focuses on mapping out and conducting a critical analysis of the processes of creating and building a body image that questions and subverts the hegemonic representations and discourses. Nowadays, the body is a frequent object of discussion in the media. Two types of discourses prevail: in the mass media, the discourse takes on an imperative note, preaching the importance of having a perfect body. In the digital media, however, it is possible to notice the emergence of a counter discourse that defends other types of bodies, which escape the rules that govern the ideal body . This Master s thesis aims to map out the multiplicity of images and discourses emerging in the cyberspace. The concept of cyberspace adopted was the one defined by Leão: a gigantic, almost endless maze of interactions typical of contemporary times, a network composed of hardware, software, people and groups. The research focuses on the following topics of discussion: daily life, body acceptance, fashion, health, self-esteem, prejudice, and respect. The theoretical frameworks adopted were: process analysis and criticism theories (Salles and Leão); body, image and power (Foucault); social networks (Costa); communication devices (Prado); body images (Sant Anna, Ortega and Vigarello). The methodology consisted of literature review; identification, selection and analysis of documents published in the social networks included in the study; image research (iconology) associated with art projects related to the concept of obese bodies; and mapping of images and imaginary as a method of knowledge production (Leão). Grounded in the idea of image, talk spaces and power (Foucault), the research shows the importance of building an imaginary. Through the analysis of documents published in these networks (photographs, records of discussions, among others), it was possible to map out the complexities of the issues involving the authors and groups in the plus size universe. Among the findings, the mapping of images and discourses conducted in this research shows that the creation of an alternative, subversive and politically engaged imaginary is essential to promote the freedom of expression and communication regarding the body that does not conform to established standards